ANALYSIS AND CALCULATION METHODS OF PROTECTIVE GROUNDING PRYSTROYUELEKTROUSTANOVOK - and (Municipal economy of cities. Series: «Economy science», 2013)
The methods of calculating the protective grounding of electrical devices. Definitely advantages and disadvantages of the methods set out priorities for the use of these methods of calculation.